Assessment of Enrofloxacin Usage and Residue Levels of Enrofloxacin-Ciprofloxacin in Breast and Liver Tissues of Commercial Broilers Sold in Kampala-Uganda - Munanura EI; Ntale M; Wasswa J; Kaggwa B (Infection and Drug Resistance, 2023)
Edson Ireeta Munanura,1 Muhammad Ntale,2 John Wasswa,2 Bruhan Kaggwa1 1Department of Pharmacy, School of Health Sciences, College of Health Sciences, Makerere University, Kampala, Uganda; 2Department of Chemistry, School of Physical Sciences, College of Natural Sciences, Makerere University, Kampala, UgandaCorrespondence: Edson Ireeta Munanura, Tel +256740511609, Email eimunanura@gmail.comBackground: Human exposure to veterinary drugs like fluoroquinolones occurs due to the presence of their residues in foods from animal sources in varying concentrations. The existence of antibiotic residues in foodstuffs can pose great public health problems to consumers. This study aimed to assess enrofloxacin use patterns and assess residue levels of enrofloxacin/ciprofloxacin in breast muscle and liver tissues of broiler chickens sold for consumption in Kampala capital city.Methods: This was a cross-sectional study that involved both field survey and laboratory-based methods. The field study involved the use of qualitative and semi-quantitative data collection tools to interview 34 broiler farmers and 10 veterinary drugs vendors. For the determination of enrofloxacin/ciprofloxacin levels, 68 chicken breast and liver tissue samples were collected from main markets in Kampala over one month and analyzed using HPLC-UV.Results: Enrofloxacin was the most used antibiotic (100%) for the management of poultry diseases, majorly respiratory diseases (100%), salmonella infections (40%), and disease prevention (60%). Over 76% of the farmers knew the meat withdrawal time (WDT) for enrofloxacin, but none of them adhered to this. Over 70% of the farmers reported that the veterinary drugs vendors were not providing meat WDT information. Enrofloxacin/ciprofloxacin residues were identified in 35.3% (12/34) of the muscle and 38.2% (13/34) of the liver tissues analyzed. Of those muscle and liver tissue samples that tested positive, 25% (3/12) and 38.5% (5/13) respectively had drug concentrations higher than the recommended Maximum Residue Limits. The overall mean enrofloxacin/ciprofloxacin concentration in the chicken muscle and liver tissues was 83.6 (± 34.5) μg/kg and 171.5 (± 75.9) μg/kg.Conclusion: This observed presence of enrofloxacin/ciprofloxacin levels above safety requirements is attributable to inadequate medicines use information provided by veterinary drugs vendors to farmers and also to the non-compliance of some farmers to meat WDT due to the economic implications.Keywords: withdrawal time, maximum residue limits, enrofloxacin, food safety